Fluorescent Amplified Fragment Length Polymorphism and Pulsed-Field Gel Electrophoresis Analyses of Multidrug Resistant Salmonella enterica serotype Typhi from different geographical endemic regions in Asia - Thong, Kwai Lin; Elgar, Sleman; Bhutta, Zulfikar; Yasin, Rohani; Schreiber, Edgar (Malaysian Society for Molecular Biology and Biotechnology, 2003)
Sixty-three isolates of Salmonella enterica serotype Typhi (S.typhi) from sporadic cases of typhoid fever obtained from Malaysia (n=6), Vietnam (n=13), India (n=8) and Pakistan (n=36) were characterized by phage typing, drug-susceptibility testing, amplified fragment length polymorphism (AFLP) and pulsed-field gel electrophoresis (PFGE) with restriction endonuclease, XbaI. The strains analyzed were mostly resistant to ampicillin, co-trimoxazole, tetracycline and chloramphenicol. These strains were represented by phage types, E1, E9, 46, J1, VNS and UVS. PFGE analysis showed that multidrug resistant (MDR) strains isolated in different countries and at different periods were genetically very homogenous where 90% of the strains analyzed had very closely related XbaI patterns. AFLP was able to subtype 42 clonally related MDR strains (represented by 8 PFGE patterns) into 16 profiles. Cluster analysis based on the AFLP and PFGE data using unweighted pair group mean averages could differentiate MDR strains from different geographical region and that the drug-sensitive strains were in a distinct cluster. The clustering of MDR strains from each country and the presence of a dominant XbaI–PFGE pattern indicated that the MDR S.typhi had probably been spread clonally in these countries. AFLP is clearly more discriminative than PFGE in differentiating the MDR S.typhi, hence providing an alternative, sensitive method for detailed analysis of the multidrug resistant strains.